8(x-2)+20=40+x

Simple and best practice solution for 8(x-2)+20=40+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-2)+20=40+x equation:



8(x-2)+20=40+x
We move all terms to the left:
8(x-2)+20-(40+x)=0
We add all the numbers together, and all the variables
8(x-2)-(x+40)+20=0
We multiply parentheses
8x-(x+40)-16+20=0
We get rid of parentheses
8x-x-40-16+20=0
We add all the numbers together, and all the variables
7x-36=0
We move all terms containing x to the left, all other terms to the right
7x=36
x=36/7
x=5+1/7

See similar equations:

| 3(x+2)+20=40+x | | 0.17x^2-20x+400=0 | | 250x+30x=60 | | 19+5x=8x-8 | | 0.41x=0.4x+120,000 | | 3t±8=6 | | 5p-3=-18 | | a^2+2a+3=0 | | 0.03x+x=100 | | 2x-8=4÷2+4= | | 2x-8=4÷2 | | b/10=5/3 | | 5x=2x+1000 | | 1-11(n-9)=-4(n+3) | | 11b-110=-(1-11b) | | 11b-110=-1-11b) | | 7(1+5n)=-7(10-4n)+7 | | 11(-6n-2)-2n=2n+12(9-8n) | | 3(12x-9)=3(11+10x)+10x | | -3(-2x+11)-7(-x-3)=9x+2x | | -2(-9n-8)=-(-10n-8) | | -(p+4)=-2(2p+8) | | 0.25(4x-3)=0.05(20x-9) | | 3^1/4×2^3/4=x | | 4(m+6)=8(m+1) | | 12x-2(12x-2)=-10(7x-12) | | (5u-30)(u^2+10u+24)=0 | | x/5=13/10 | | x^2=10√6 | | -3r+8r=6(1+r)-6(1+4r) | | 4^x-6.2^x=16 | | -11-2(1+9v)=-3(9v+10)+8v |

Equations solver categories